Приводимость нелинейных почти периодических систем разностных уравнений, заданных на торе - Самойленко, А.М.; Мартынюк, Д.И.; Перестюк, Н.А. (Український математичний журнал, 1994)
Sufficient conditions are established for the reducibility of a nonlinear system of difference equations x(x+1) = x(1)+ω+P(x(t),t)+λ, where P(x,t) is a function 2π-periodic in xi(i=1,...,n) and almost periodic in tt with a frequency basis αα, to the system y(t+1)=y(t)+ω.